Truncated DNM1 variant underlines developmental delay and epileptic encephalopathy - Afsar, Tayyaba; Huang, Xiaoyun; Shah, Abid Ali; Abbas, Safdar; Bano, Shazia; Mahmood, Arif; Hu, Junjian; Razak, Suhail; Umair, Muhammad (Frontiers in Pediatrics, 2023)
Background: Developmental and epileptic encephalopathies (DEEs) signify a group of heterogeneous neurodevelopmental disorder associated with early onset seizures accompanied by developmental delay, hypotonia, mild to severe intellectual disability and developmental regression. Variants in the DNM1 has been associated with autosomal dominant DEEs type 31A and autosomal recessive DEEs type 31B. Methods: In the current study, a consanguineous Pakistani family consisting of a proband (IV-2) was clinically evaluated and genetically analyzed in manifesting severe neurodevelopmental phenotypes. WES followed by Sanger sequencing was performed to identify the disease-causing variant. Furthermore, 3D protein modeling and dynamic simulation of wild and mutant proteins along with reverse transcriptase (RT) based mRNA expression was checked using standard methods. Results: Data analysis of WES revealed a novel homozygous nonsense variant (c.1402G>T; p. Glu468*) in exon 11 of the DNM1 gene that was predicted, as pathogenic class I. Variants in the DNM1 have been associated with DEE-type 31A and B. Different bioinformatics prediction tools and ACMG guidelines were used to verify the identified variant. Sanger sequencing was used to validate the disease causing variant. Our approach validated the pathogenesis of the variant as a cause of heterogeneous neurodevelopmental disorders. In addition, 3D protein modeling showed that the mutant protein would lose most of the amino acids and might not perform the proper function if skipped the surveillance nonsense-mediated decay (NMD) mechanism. Molecular Dynamics analysis showed varied trajectories of wild and mutant DNM1 proteins in terms of RMSD (root mean square deviation), RMSF (root mean square fluctuation) and Rg (radius of gyration). Similarly, RT-qPCR revealed a substantial reduction of the DNM1 gene in the index patient. Conclusion: Our finding further confirms the association of homozygous, loss-of-function variants in DNM1 associated with DEE type 31B. The study expands the genotypic and phenotypic spectrum of pathogenic DNM1 variants related to DNM1-associated pathogenesis.